Prevalence of incidental humeral intracondylar fissures in brachycephalic breed dogs in CT studies. Issue 2 (7th December 2022) - Franklin, Chantelle; Herrtage, Michael; Harris, Karen; Genain, Marie‐Aude
Abstract: Humeral intracondylar fissures (HIF) have been predominantly reported in spaniel breeds and proposed to be possible risk factors for humeral condyle fractures (HCF). We hypothesized that the prevalence of incidental HIF in French Bulldogs may be greater than that of other brachycephalic breeds. A retrospective, observational, prevalence study was performed using CT examinations of French bulldogs and other brachycephalic breed dogs presenting for an unrelated condition. Two European College of Veterinary Diagnostic and Imaging‐certified radiologists reviewed the images of the humeral condyles of these dogs. A classification system was devised to grade the findings. We considered a Score 1 to be normal, Score 2 to have centralised sclerosis, Score 3 to have a partial fissure and Score 4 to have a complete fissure. A total of 228 elbows were reviewed from 122 dogs. Of this population, 145 elbows were from French Bulldogs, 54 were from Pugs, and the remainder were from a mix of other brachycephalic breeds. The prevalence of HIF (score 3 or 4) in elbows of the French bulldog, pug and other breed groups was 6.9% (CI 2.8–11%), 5.6% (CI 0–11.7%), and 3.4% (CI 0–10.15%), respectively. At a dog level, the prevalence of HIF (score 3 or 4 present in at least one elbow) was found to be 11.8% (CI 4.6–19%) in French Bulldogs, 11.1% (CI 0–22.9%) in Pugs, and 5.26% (CI 0–15%) in the other breed group. There was no significant difference between the breed groups. The inter‐reviewer reliability for CT scoring of HIF based on Cohen's weighted kappa was low at 0.19.